2009
DOI: 10.3928/00485713-20090514-01
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Posttraumatic Stress Disorder

Abstract: <p>Posttraumatic stress disorder (PTSD) is highly prevalent and has substantial economic and social consequences. In this article, we review the epidemiology of PTSD. We begin by summarizing the evidence about the prevalence and correlates of traumatic event exposure. Next, we discuss the prevalence of PTSD, the conditional probability of PTSD given specific traumatic event exposure, the correlates, and demographic distribution of PTSD, and the trajectory of PTSD over the life course. Lastly, we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
3
23
0
2
Order By: Relevance
“…This study aimed at reevaluating the association between levels of DSM 5 PTSD symptoms with several of these variables, including, gender, peritraumatic dissociation, social support, levels of objective and subjective threat, and trait tendency for forgiveness -variables which have been associated with PTSD symptoms in previous studies prior to modifications in the DSM 5 for PTSD (Ballenger et al 2000;Brewin et al 2000;Norris et al 2002;Ozer et al 2003;Gil 2005;Kessler et al 2005;Johnson et al 2009;Jaksic et al 2012). Specifically, 501 Israeli civilians living in missile attack areas were assessed during the ongoing Gaza war.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed at reevaluating the association between levels of DSM 5 PTSD symptoms with several of these variables, including, gender, peritraumatic dissociation, social support, levels of objective and subjective threat, and trait tendency for forgiveness -variables which have been associated with PTSD symptoms in previous studies prior to modifications in the DSM 5 for PTSD (Ballenger et al 2000;Brewin et al 2000;Norris et al 2002;Ozer et al 2003;Gil 2005;Kessler et al 2005;Johnson et al 2009;Jaksic et al 2012). Specifically, 501 Israeli civilians living in missile attack areas were assessed during the ongoing Gaza war.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the field (e.g., Ozer et al 2003;Johnson and Thompson 2008;Johnson et al 2009) have identified several significant variables as risk factors, mainly a history of traumatic exposure, age, and gender (with female at higher risk for PTSD), as well as genetic factors (e.g., Ballenger et al 2000;Norris et al 2002;Kessler et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, exposure to a traumatic event by itself is not a suffi cient precondition for subsequent PTSD. Th e professional literature has demonstrated that only a minority of individuals who were exposure to trauma developed PTSD or other trauma-related disorders (Ozer, Best, Lipsey, Weiss 2003;Johnson, Th ompson 2008;Johnson, Maxwell, Galea 2009). Aside from the exposure to the traumatic event, other variables have been examined as PTSD risk factors.…”
Section: Post-trauma C Stress Disorder and Acute Stress Disorders Andmentioning
confidence: 99%
“…Sexueller Missbrauch erhöht das Risiko für spätere mentale Erkrankungen um das 2,4-fache, bei physischem Missbrauch steigt das Risiko um das 1,5-fache an [22]. Psychische Erkrankungen als wahrscheinliche Folge von Traumata in Kindheit und Adoleszenz beinhalten sowohl internalisierende Probleme wie Depression und Anpassungsstörungen [31,47,52] als auch externalisierende Auffälligkeiten wie Probleme mit Peers, aggressives und dissoziales Verhalten [7]. Zudem zeigen misshandelte Kinder und Jugendliche oft Beeinträchtigungen der Exekutivfunktionen (beispielsweise Aufmerksamkeit oder Verarbeitungsgeschwindigkeit) sowie der motorischen und sprachlichen Fähigkeiten [15,19,45] fanden Zusammenhänge zwischen verschiedenen traumatischen Erfahrungen und höheren klinischen Werten bezüglich Depression, Wut, posttraumatischem Stress und Dissoziation während Resilienz-Faktoren verhältnismässig gering ausgeprägt waren.…”
Section: Introductionunclassified
“…Das Auftreten einer Posttraumatischen Belastungsstörung (PTBS) ist nach physischen, und hierbei vor allem nach sexuellen Angriffen mit einer Prävalenzrate von 55 % besonders hoch [31]. Gerade im Kindes-und frühen Jugendalter (unter 14 Jahren) werden traumatische Erfahrungen häufig mit einer PTBS assoziiert [41].…”
Section: Introductionunclassified